Design and research of cable channel fire extinguishing temperature sensing module. Issue 1 (1st October 2022) - Liu, Sanwei; Duan, Xiaoli; Huang, Fuyong; Duan, Jianjia; Gong, Liang; He, Du
Abstract: As the core equipment of urban power supply, once the cable is on fire, it will have a great impact on the economy and people's livelihood. Cable passage fire extinguishing equipment is a reliable infrastructure to eliminate cable fire, and detection components are the key to correct and timely action of fire extinguishing equipment. This paper designs a temperature detection module based on DS18B20, and discusses the design principle from the aspects of internal structure, command sequence, signal mode and so on.